Dynamic Anterior Shoulder Stabilization With the Long Head of the Biceps Tendon: A Biomechanical Study. Issue 6 (May 2019) - Mehl, Julian; Otto, Alexander; Imhoff, Florian B.; Murphy, Matthew; Dyrna, Felix; Obopilwe, Elifho; Cote, Mark; Lädermann, Alexandre; Collin, Philippe; Beitzel, Knut; Mazzocca, Augustus D.
Background: The concept of dynamic anterior shoulder stabilization (DAS) combines a Bankart repair with the additional sling effect of the long head of the biceps (LHB) tendon to treat anterior glenohumeral instability. This surgical technique was created to close the gap between the indications for isolated Bankart repair and those requiring bone transfer techniques. Purpose: To biomechanically investigate the stabilizing effects of the DAS technique in comparison with the standard Bankart repair in different defect models. Study Design: Controlled laboratory study. Methods: Twenty-four fresh-frozen cadaveric shoulders (mean ± SD age, 60.1 ± 8.6 years) were mounted in a 6 degrees of freedom shoulder testing system. With cross-sectional area ratios, the rotator cuff muscles and LHB tendon were loaded with 40 N and 10 N, respectively. Anterior and inferior glenohumeral translation was tested in 60° of abduction and 60° of external rotation (ABER position) while forces of 20 N, 30 N, and 40 N were applied to the scapula in the posterior direction. Total translation and relative translation in relation to the native starting position were measured with a 3-dimensional digitizer. Maximal external rotation and internal rotation after application of 1.5-N·m torque to the humerus were measured. All specimens went through 4 conditions (intact, defect, isolated Bankart repair, DAS) and were randomized to 1 of 3 defect groups (isolated Bankart lesion, 10% anterior glenoid defect, 20% anterior glenoid defect). The DAS was performed by transferring the LHB tendon through a subscapularis split to the anterior glenoid margin, where it was fixed with an interference screw. Results: Both surgical techniques resulted in decreased anterior glenohumeral translation in comparison with the defect conditions in all defect groups. As compared with isolated Bankart repair, DAS showed significantly less relative anterior translation in 10% glenoid defects at translation forces of 20 N (0.3 ± 1.7 mm vs 2.2 ± 1.8 mm, P = .005) and 30 N (2.6 ± 3.4 mm vs 5.3 ± 4.2 mm, P = .044) and in 20% glenoid defects at all translation forces (20 N: –3.2 ± 4.7 mm vs 0.8 ± 4.1 mm, P = .024; 30 N: –0.9 ± 5.3 mm vs 4.0 ± 5.2 mm, P = .005; 40 N: 2.1 ± 6.6 mm vs 6.0 ± 5.7 mm, P = .035). However, in 20% defects, DAS led to a relevant posterior and inferior shift of the humeral head in the ABER position and to a relevant increase in inferior glenohumeral translation. Both surgical techniques did not limit the rotational range of motion. Conclusion: In the context of minor glenoid bone defects, the DAS technique demonstrates less relative anterior translation as compared with an isolated Bankart repair at time zero. Clinical Relevance: The new DAS technique seems capable of closing the gap between the indications for isolated Bankart repair and bone transfer techniques.